Myth and Social Consciousness in Wole Soyinka’s Alapata Apata - Afolayan, Kayode (Imbizo, 2021)
The study of myths—their relevance and importance—has always generated interest among scholars over the ages. After the initial engagements before the twentieth century when most interventions, from scholars such as Xenophanes, Plato and Euhemerus, pronounced myths as intangible, many writers today have continued to use myth as an anchor of their works. In Africa, writers like Wole Soyinka have deployed myths in the interrogation of crises in the postcolonial space. Since the publication of his seminal work, Myth, Literature and the African World (1992), which laid out the essences of primordial forms in his Yoruba tradition, Soyinka has continued to deploy the capacities of those primordial “literary” forms, particularly Ogun, in his interrogation and interventions on diverse conditions in the African landscape. Using Alapata Apatata, Soyinka’s latest play, where the issues of culture and its renaissance, survival and politics in his home country generate great concern, this article re-examines the playwright’s ambivalent attraction to myth and its use to intervene in the diverse social contradictions in the postcolonial space. The author, after establishing the link between Ogun and Alaba, the protagonist in the play, identifies Soyinka’s paradigm shift in a new twist that sees Ogun in the comedy terrain. The conclusion of the paper draws on Soyinka’s “mythmaking” or “mythbreaking” in the play in a way that conceptualises the evolutionary trend in the playwright’s exploration of Ogun.